PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE SCRIPT TERHADAP HASIL BELAJAR IPS TERPADU SISWA KELAS VII SMP NEGERI 28 KABUPATEN TANJUNG JABUNG TIMUR - Eva Anggraini; Lili Andriani (SJEE (Scientific Journals of Economic Education), 2020)
This type of research is experimental research. The population in this study was 435 people. The sample of this study was 78 students, consisting of 38 students of class VIIB and 40 students of class VIIC. The results showed that (1) the learning outcomes of students who were taught using the cooperative learning model type Cooperative Script were 13 students. who obtained a score above the KKM, namely 75. From the 40 questions that the researcher asked, it was known that the highest score for the students' answers was 35 with a score of 87.5; as many as 4 students, while the lowest score for student answers was 13 with a value of 32.5; namely as many as 1 student, (2) student learning outcomes taught using conventional learning models are 11 students who get a score above the KKM, which is 75. Of the 40 questions that the researcher asked, it is known that the highest score for student answers was 32 with a value of 80, namely as many as 3 students. While the lowest score for student answers was 13 with a value of 32.5; namely as many as 1 student, and (3) student learning outcomes taught using cooperative learning model type Cooperative Script higher than student learning outcomes taught using conventional learning models. This is evidenced by the value of t count>, which is 3.2 > 1.9917.